If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12m + -7 = 5m + 28 Reorder the terms: -7 + 12m = 5m + 28 Reorder the terms: -7 + 12m = 28 + 5m Solving -7 + 12m = 28 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. -7 + 12m + -5m = 28 + 5m + -5m Combine like terms: 12m + -5m = 7m -7 + 7m = 28 + 5m + -5m Combine like terms: 5m + -5m = 0 -7 + 7m = 28 + 0 -7 + 7m = 28 Add '7' to each side of the equation. -7 + 7 + 7m = 28 + 7 Combine like terms: -7 + 7 = 0 0 + 7m = 28 + 7 7m = 28 + 7 Combine like terms: 28 + 7 = 35 7m = 35 Divide each side by '7'. m = 5 Simplifying m = 5
| -5.7m-2.2m=23.7 | | 7.2=8.6-0.7x | | f(x+6)=5x+5 | | 2x^2+9x+8= | | 5x+4-2=(x+8) | | 6s+(4s-20)=450 | | 7x-3=4-2x | | -6+4(3x-13)=82 | | 2*y-3*y=5 | | 8x+1=1.528 | | -2m-8m=10 | | 24x=24x-27 | | (x+7)2+(y-1)2=32 | | x=52.5(2/5) | | u^2=3u | | k(x)=2x^2+33x-54 | | x=40(2/5) | | 11=11-10b+2b | | s-3=-5 | | 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) |